Enhanced metabolic effect of erythropoietin and keto acids in CRF patients on low-protein diet: Czech multicenter study - Teplan, Vladimír; Schück, Otto; Knotek, Antonín; Hajný, Jan; Horácková, Miroslava; Kvapil, Milan; Czech multicenter study (American journal of kidney diseases, 2003)
BACKGROUND: Our study is designed to establish whether supplementation with erythropoietin (EPO) exerts additional beneficial metabolic effects in patients with chronic renal failure (CRF) treated with keto acids (KAs) on a low-protein diet (LPD). METHODS: A long-term, prospective, randomized study was designed to use three therapeutic protocols: (A) EPO plus KAs plus LPD (group I), (B) EPO plus LPD (group II), and (C) LPD (group III). One hundred eighty-six randomly selected patients (90 men, 96 women; age, 22 to 78 years) with a creatinine clearance of 22 to 36 mL/min were monitored at the beginning and at every 6 months for 3 years. RESULTS: During the study period, glomerular filtration rate measured as inulin clearance decreased slightly (from 26.2 +/- 3.4 to 23.4 +/- 4.1 mL/min in group I), 27.4 +/- 4.8 to 20.2 +/- 4.4 mL/min in group II, and 26.8 +/- 3.6 to 17.4 +/- 4.1 mL/min in group III; P < 0.01). Serum urea levels also declined (P < 0.01), more pronouncedly in group I (P < 0.025). In group I, there was a significant increase in levels of leucine (P < 0.01) and albumin (P < 0.01) and a decrease in proteinuria (P < 0.01). Analysis of the lipid spectrum showed a mild, yet significant, decrease in total cholesterol and low-density lipoprotein cholesterol levels (P < 0.025), more pronounced in group I. In group I, there was a decrease in plasma triglyceride levels (from 362.85 +/- 115.05 mg/dL [4.1 +/- 1.3 mmol/L] to values as low as 203.55 +/- 70.80 mg/dL [2.3 +/- 0.8 mmol/L]; P < 0.01), whereas high-density lipoprotein cholesterol levels increased (from 34.75 +/- 7.72 mg/dL [0.9 +/- 0.2 mmol/L] to 46.33 +/- 7.72 mg/dL [1.2 +/- 0.2 mmol/L]; P < 0.025). Mean arterial blood pressure was stable. CONCLUSION: EPO supplementation in patients with CRF administered KAs potentiates the beneficial effects on metabolism of proteins, amino acids, and lipids. Long-term coadministration of EPO, KA, and LPD was associated with a delay in progression of renal failure and reduction in proteinuria.
Keywords: nízkoproteinová dieta; lidé středního věku; prospektivní studie; krevní tlak; ketokyseliny; erythropoetin; rekombinantní proteiny; Erythropoietin; Glomerular Filtration Rate; Blood Pressure; Male; krevní proteiny; Kidney Failure, Chronic; dospělí; Recombinant Proteins; Diet, Protein-Restricted; lidé; senioři; Prospective Studies; Aged; Lipids; Czech Republic; Keto Acids; Česká republika; Blood Proteins; ženské pohlaví; hodnoty glomerulární filtrace; Adult; lipidy; chronické selhání ledvin; mužské pohlaví; Middle Aged; Humans; Female